Microbial analysis of tap water collected from selected upazillas of Jamalpur, Tangail, Kishoreganj and Netrokona districts of Bangladesh - Champa, Hosneara; Kabir, S M Lutful (Asian Journal of Medical and Biological Research, 2018)
The present study was undertaken to analyze the microbial quality of tap water samples obtained from different upazilla markets of Jamalpur, Tangail, Kishoreganj and Netrokona districts. For achieving the above mentioned objectives, 20 tap water samples were collected and the methods of heterotrophic plate count (HPC) and total coliform count (TCC) were applied. Moreover, isolated E. coli from tap water samples were characterized by using biochemical test, molecular method and antimicrobial susceptibility tests. HPC was highest in market tap water collected from Sarishabari of Jamalpur district and TCC was highest in market tap water collected from Durgapur of Netrokona district. The geometric mean of HPC of Jamalpur, Tangail, Kishoreganj and Netrokona districts water were 4.2x107, 2.7x107, 2.4x107 and 4.4x107 CFU/ml respectively. Out of 13 isolates of E. coli, 13 isolates were amplified by using 16S rRNA gene based PCR. The antimicrobial susceptibility pattern showed that the isolates were highly resistant to amoxicillin. Most of the E. coli isolates were susceptible to tetracycline, azithromycin, streptomycin, norfloxacin and ciprofloxacin. Furthermore, a few E. coli isolates were intermediate resistant to erythromycin and gentamycin. Moreover, out of 13 E. coli isolates 2 (15.4%) isolates were detected as multidrug resistant. This study indicated the presence of multidrug resistant E. coli isolates in tap water in Jamalpur, Tangail, Kishoreganj and Netrokona districts that warrant particular attention. Asian J. Med. Biol. Res. June 2018, 4(2): 193-200